Water quality assessment in shrimp culture areas of Soc Trang province : - Olueadamilare, Aina Ayyotunde (Trường Đại học Cần Thơ, 2019)
This research is performed to investigate water quality in the shrimp culture areas of Soc Trang Province in order to provide a baseline for water quality management ensuring a sustainable shrimp culture in the area.